Testing Trade-Off and Pecking Order Predictions About Dividends and Debt. (16th June 2015) - Fama, Eugene F.; French, Kenneth R.
Abstract : Confirming predictions shared by the trade-off and pecking order models, more profitable firms and firms with fewer investments have higher dividend payouts. Confirming the pecking order model but contradicting the trade-off model, more profitable firms are less levered. Firms with more investments have less market leverage, which is consistent with the trade-off model and a complex pecking order model. Firms with more investments have lower long-term dividend payouts, but dividends do not vary to accommodate short-term variation in investment. As the pecking order model predicts, short-term variation in investment and earnings is mostly absorbed by debt.